Molecular ecological analysis of methanogenic communities in terrestrial and submarine permafrost deposits of Siberian Laptev Sea area - Feige, Katharina (2009)
Despite general concern that the massive deposits of methane stored under permafrost underground and undersea could be released into the atmosphere due to rising temperatures attributed to global climate change, little is known about the methanogenic microorganisms in permafrost sediments, their role in methane emissions, and their phylogeny. The aim of this thesis was to increase knowledge of uncultivated methanogenic microorganisms in submarine and terrestrial permafrost deposits, their community composition, the role they play with regard to methane emissions, and their phylogeny. It is assumed that methanogenic communities in warmer submarine permafrost may serve as a model to anticipate the response of methanogenic communities in colder terrestrial permafrost to rising temperatures. The compositions of methanogenic communities were examined in terrestrial and submarine permafrost sediment samples. The submarine permafrost studied in this research was 10°C warmer than the terrestrial permafrost. By polymerase chain reaction (PCR), DNA was extracted from each of the samples and analyzed by molecular microbiological methods such as PCR-DGGE, RT-PCR, and cloning. Furthermore, these samples were used for in vitro experiment and FISH. The submarine permafrost analysis of the isotope composition of CH4 suggested a relationship between methane content and in situ active methanogenesis. Furthermore, active methanogenesis was proven using 13C-isotope measurements of methane in submarine permafrost sediment with a high TOC value and a high methane concentration. In the molecular-microbiological studies uncultivated lines of Methanosarcina, Methanomicrobiales, Methanobacteriacea and the Groups 1.3 and Marine Benthic from Crenarchaeota were found in all submarine and terrestrial permafrost samples. Methanosarcina was the dominant group of the Archaea in all submarine and terrestrial permafrost samples. The archaeal community composition, in particular, the methanogenic community composition showed diversity with changes ...